THE DEVELOPMENT OF "A THOUSAND SEMLIRO STONE OF KUDUS" TOURISM THROUGH A BRANDING STRATEGY - Pratiwinindya, Ratih Ayu; Rafinda, Ascariena; Rebowo, Tjatur; Triyanto, Triyanto (Arty: Jurnal Seni Rupa, 2020)
The tourism sector is one of the national priorities which is a sustainable source of increasing national and regional income. Ã¢â‚¬Å“Bukit Seribu Batu SemliroÃ¢â‚¬Â is one of the new tourism destination in Kudus Regency which has great potential to improve the welfare of the surrounding community and regional income. As a new destination, of course, there are many things that need to be prepared and developed. Based on these facts, several weaknesses were found in the management of this new tourist destination and they still do not have the capability in tourism branding and marketing strategies so that the attraction of this tourism destination is less well known in the community and donÃ¢â‚¬â„¢t have a high profit. Therefore, a strategy is needed to make this potential destination better known by the public and have a high income. This study aims to explain how the destination branding strategy can be pursued by the owner and his management, to promote the potential owned by Seribu Batu Semliro. The result of this research is visual branding in the form of brand identity is one of the tourism branding srategies that seeks to build a uniqueness or specificity of Seribu Batu Semliro, also become a strategy to make the Seribu batu Semliro as a superior tourist destination for long period of time in Kudus.